Fish in Kongsfjorden under the influence of climate warming - Gorska, Natalia; Schmidt, Beata; Węsławski, Jan Marcin; Grabowski, Miłosz; Dragan-Górska, Agata; Szczucka, Joanna; Beszczynska-Möller, Agnieszka (Frontiers in Marine Science, 2023)
Introduction: Kongsfjorden is under impact of climate warming which fosters the increase of abundance of Atlantic fish (e.g. Atlantic cod, Gadus morhua), non endemic for Kongsfjorden. The growth and high predation potential of Atlantic fish may affect the survival of polar cod (Boreogadus saida), native species of the Kongsfjorden, a species with ecological and economic value. This means that it is important to monitor the impact of climate change on the fjord fish community. This, as well as the experience of the successful use of hydroacoustic techniques in the fjord, encouraged us to continue in 2022 the hydroacoustic study of fish started in 2013 and 2014. Our main goal was to understand and confirm how the fish community in the Kongsfjorden has changed over the last decade under the influence of global warming. Methods: Our approach included not only to replicate in 2022 the previous research conducted in 2013 and 2014, basing on the same methodology for collecting and analyzing hydroacoustic data, but also to compare the newly acquired data with the results available in the previous publications. The histograms of fish target strength (a measure of sound backscatter by an individual) were analyzed and the fish spatial distribution (in regard to thermohaline structure and “predator-prey” relationships) was acoustically observed. Results: The presence of native polar cod and non endemic species Atlantic cod in the Kongsfjorden was shown. Furthermore, during the study period, an increase in fish size diversity was observed - what suggests change in food web and decline in native polar cod. It was confirmed that the process of establishment of non-Arctic species Atlantic cod in Kongsfjorden continues. Discussion: We went beyond the spatial and temporal constraints of previous Kongsfjorden studies, taking into account fjord fish communities over a wider area and over the long term. Therefore, our understanding of climate warming impact on the fish community of Kongsfjorden has been deepen. The further progress necessitates annual hydroacoustic observing the fjord fish community accompanied by biological sampling.